Discipline and Motivation as Determining Factors for Teacher Performance in Elementary Schools - Lestari, Asri Ayu; Habiburahman (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study analyzes the relationship between discipline and work motivation and teacher performance, both individually and simultaneously, in the context of elementary education. Methods a quantitative correlational associative design was used. All 30 teachers at public elementary school 3 Negara Ratu, South Lampung were selected via census sampling. Data were collected using a validated 30-item likert-scale (1-5) questionnaire and analyzed using multiple linear regressions, preceded by normality (Shapiro-Wilk), multicollinearity, and heteroscedasticity tests. Results is work discipline and motivation simultaneously and significantly influence teacher performance (F = 14.059; p = 0.000 < 0.05). Work discipline (β = 0.407; p = 0.033) and work motivation (β = 0.498; p = 0.019) each have a significant positive effect. The coefficient of determination (R² = 0.510) indicates that both variables explain 51% of the variance in teacher performance. Conclusion is work discipline and work motivations are key determinants of teacher performance. Schools should enforce consistent work regulations and cultivate motivational environments to improve educational quality.